Effect of temperature and pH value on the rate of corrosion / Mohd Khairul Anuar Suudi - Suudi, Mohd Khairul Anuar (2016)
Transmission gas pipeline is important part in oil and gas industries while a carbon steel is a primary material for construction the pipeline due its low cost and availability, but it is very susceptible to corrosion in C02 environment. There are several types of corrosion can occur in pipelines which is effect to the production of the oil and gas. Carbon dioxide (CO2) corrosion one of the type of corrosion that occur in oil and gas industries that causes the pipelines failures. Aqueous carbon dioxide (carbonic acid) is corrosive and corrodes the carbon steel pipelines and it is influenced by several environment factors such as temperature, pH, and oxygen content. In this research, that factors temperature and pH are focusing in effect of corrosion rate. Main of the experiment are to study the effect of the temperature and pH in to the rate of corrosion. This experiment set up with the different temperature and pH Value such as 30°c, 50°c and 80°c and pH like pH 3, pH 5, pH 7, pH 9 and pH 11. In this research, the samples will measure their weight before and after experiment. Then, weight loss of the every samples are recorded to calculate the rate of corrosion. Based on the research that corrosion can occur when form higher temperature condition and low of pH environment. As the temperature increase, the corrosion rate will increase due to the dissolution of iron ion and formation of weak carbonic acid. In acidic condition, the present of H+ ions make H+ reduction cathodic reaction and corrosion rate is occur due to low of pH.